(untitled) (International Journal of Engineering and Computer Science, 2015)
The objective of this paper is to design and build a portable assistive device for narcolepsy patients in order to help them to feel comfortable and lead a normal life, so people can be independent. A narcoleptic person suffers from a brain disorder that causes uncontrolled sleepiness because of over emotions, anger etc. This device provides real time monitoring system and alerts if they are in state of sleep and it also reduces the parameters causing narcolepsy (such as excessive vibration, heavy noise etc) . This paper gives brief description about an assistive system designed for narcoleptic patients in order to help them to lead a normal life